CLOWN VS RAPPER: (INVECTIVES IN ONLINE AND OFFLINE RAP BATTLES) / КЛОУН VS РЭПЕР: (ИНВЕКТИВЫ В ОНЛАЙН И ОФЛАЙН РЭП-ПОЕДИНКАХ) - SEMENOVA ELENA A. / СЕМЕНОВА Е.А. (Наука телевидения, 2020)
The article is devoted to identifying the reasons for the more frequent laughter among listeners, caused by invectives addressed to the opponents’ pseudonyms rather than to their real names. In this regard, much attention in the work is paid to the concept of invective associated with the art of clownery. Since the times of Ancient Greece and Rome, it was one of the most important strategies of rhetorical art; now it is a key definition of a rap battle, in which the audience witnesses not humor, but something between humor and seriousness. (The written comments of the audience can be compared with the satirical texts of folk poetry: its anonymous authors treat the depicted characters as representatives of the laugh world that do not exist in reality.) Therefore, it is no coincidence that rap duels, which are discussed in this article, are considered the heirs of the ancient poetic competitions, where participants exalted themselves by humiliating their partners. The article analyzes oral and written texts of rap battles and viewers’ comments with reference to a deep, humorous interpretation. The basis here is the Kozintsev’s metasemantic approach to the phenomenon of humor, which was not previously applied to their analysis. According to this approach, humor is explained by the ability to make fun of one’s own stupidity and auto–parody of oneself as a representative of Homo sapiens. The comic nature is especially pronounced in clowns and is extremely uncommon for participants in rap battles. In the beginning of the research, it was suggested that the rules of rap duels probably prevent comic situations from occurring during rap battles. Later, however, the author came to the conclusion that in reality, these rules provoke humorous moments, since the audience begins to transform the participants’ pseudonyms into carnival nicknames, perceiving them at an unconscious level as a game signal.